Purple urine in a patient with UTI and constipation. Issue 2 (27th February 2023) - Kannan, Lakshmi; Bauman, Allison Ann
ABSTRACT: Purple urine bag syndrome (PUBS) is a visually striking and a rare side effect in a patient with urinary tract infection where urine in the catheter bags and tubing turn purple. The urine in PUBS gets its color from the combination of two pigments, indirubin and indigo, which are breakdown products of tryptophan. The most important risk factors include long-term catheterization, female gender, chronic constipation, old age and being bed bound. Here, we present a case of PUBS in an elderly female with a history of bladder cancer that needed catheterization along with constipation.